Self-healing epoxy heat-conducting structural adhesive as well as preparation and application thereof
By using polysulfur rubber modified epoxy resin and tributylphosphine in thermally conductive structural glue, self-healing of thermally conductive structural glue is achieved, solving the problem of prone to breaking of thermally conductive structural glue in the prior art, and extending the The service life and ensures the safety and performance of the battery pack.
Patent Information
- Application Number
- CN202411376124.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The existing thermally conductive structural adhesives are prone to microcracks and fractures under the influence of thermal, mechanical and chemical factors, resulting in the threat of battery pack fixation and heat dissipation safety. The thermally conductive structural adhesives with self-healing ability have not been reported yet.
采用聚硫橡胶改性环氧树脂、柔性环氧树脂和三丁基膦等组成部分,通过在惰性气氛下进行加成反应形成二硫键,结合胺类固化剂和导热填料,形成可自愈 The combined epoxy thermal conductivity adhesive uses tributylphosphine to promote dynamic exchange reaction of disulfide bonds to achieve network structure rearrangement and self-healing.
It realizes the self-healing ability of thermally conductive structural adhesive, extends the service life, and while maintaining good bonding and thermal conductivity, it enhances the repair ability after breaking, ensuring the safety and performance of the power battery.
Smart Images

Figure BDA0005068716700000101 
Figure BDA0005068716700000111 
Figure BDA0005068716700000112
Abstract
Description
Technical Field
[0001] The invention belongs to the field of structural adhesives, and particularly relates to a self-healing epoxy-type thermally conductive structural adhesive and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, the penetration rate in the market is getting higher and higher. Power batteries as the core components of new energy vehicles have received widespread attention. Adhesives, as important auxiliary materials for power batteries, need to meet the dual requirements of high-strength bonding and suitable thermal conductivity. Epoxy adhesives have become one of the main chemical types of thermally conductive structural adhesives due to their good moisture and heat resistance, excellent shear strength and excellent insulation ability. At present, the research on epoxy-type thermally conductive structural adhesives mainly focuses on the lack of flexibility. For example, patent CN 117683499 A adds polyether and homemade epoxy curing agent to the formula to maintain high shear strength while increasing the elongation at break to more than 60%. At the same time, the thermally conductive filler in the formula also provides it with good thermal conductivity. However, during the use of structural adhesives, it is inevitable that they will be affected by various thermal, mechanical and chemical factors, which may cause microcracks, and further cause the adhesive surface to break, threatening the fixation and heat dissipation safety of the entire battery pack.
[0003] For structural adhesives with thermal conductivity, their structural rigidity provides excellent mechanical performance and aging resistance, but also poses higher challenges to their self-healing possibilities. In addition, their thermal conductivity comes from the large amount of fillers filled, which undoubtedly increases the difficulty of material self-healing. Although research on adhesives with self-healing ability has been reported one after another, most of them are concentrated in application fields such as sealants that have low requirements for structural strength and rigidity. Therefore, there are currently no reports on thermally conductive structural adhesives with self-healing ability. Summary of the invention
[0004] The purpose of the present invention is to provide a self-healing epoxy-type thermally conductive structural adhesive and its preparation, so as to solve the problem in the prior art that the thermally conductive structural adhesive fails after breaking, causing the entire battery pack to be unable to continue to work.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A self-healing epoxy thermal conductive structural adhesive comprises component A, component B and component C, which are calculated by weight as follows:
[0007] Component A: 20-40 parts of polysulfide rubber modified epoxy resin;
[0008] 3-15 parts of flexible epoxy resin;
[0009] 10-25 parts of thermal conductive filler;
[0010] Component B: 5-15 parts of amine polymer curing agent;
[0011] Component C: 0.02-0.2 parts of tributylphosphine.
[0012] The components of the polysulfide rubber modified epoxy resin are calculated by mass: 28 to 220 parts of polysulfide rubber and 100 parts of bisphenol A or F type epoxy resin; under the protection of an inert atmosphere, an addition reaction is carried out at 75 to 85° C. for 2 to 6 hours to obtain a polysulfide rubber modified epoxy resin with an epoxy equivalent of 300 to 550 g / eq and a disulfide bond content of 8 to 25%.
[0013] The disulfide bonds in the polysulfide rubber modified epoxy resin undergo a dynamic exchange reaction under the action of tributylphosphine, causing the network structure to rearrange and realize the self-healing of the epoxy-type thermal conductive structural adhesive.
[0014] The polysulfide rubber is a diethyl type terminal mercapto polysulfide, and the structural formula is: HS (RSS) m RSH; wherein: R is -C2H4-O-CH2O-C2H4-; the average molecular weight of the diethyl type terminal mercapto polysulfide is 1000 to 7500, and the -SH content is 1.1 to 2.0%;
[0015] Furthermore, the polysulfide rubber is preferably one or more selected from LP55, LP32, JLY124, and JLY155.
[0016] The epoxy equivalent of the bisphenol A or F epoxy resin is 150 to 230 g / eq;
[0017] Furthermore, the bisphenol A or F type epoxy resin is preferably one or more selected from E-51, E-44, E-55, NPEL-127E, NPEL-128E, and NPEF-170.
[0018] The flexible epoxy resin is one or more of dimer acid modified epoxy resin, polyurethane modified epoxy resin, and polyether modified epoxy resin;
[0019] Furthermore, the flexible epoxy resin is preferably one or more selected from DER-791, DER-852, DER-858, EPCO-1105, and XA-406T.
[0020] The thermal conductive filler is one or more of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, spherical boron nitride, and spherical alumina;
[0021] Furthermore, the thermally conductive filler is preferably selected from one or more of BN-SS, BN-C, and spherical boron nitride.
[0022] The amine polymer curing agent is one or more of a polyamide curing agent, a polyetheramine curing agent, a fatty amine polymer curing agent, an alicyclic amine polymer curing agent, and an aromatic amine polymer curing agent;
[0023] Furthermore, the amine polymer curing agent is preferably one or more selected from JH-5140, JH-5150, JH-5300E, and GPM-800.
[0024] The tributylphosphine acts as a self-healing accelerator in the reaction.
[0025] A method for preparing a self-healing epoxy thermally conductive structural adhesive is as follows:
[0026] Component A and component B are mixed according to the epoxy group-active hydrogen equimolar equivalents, and then component C is added and mixed evenly, and cured at 20-30° C. and 0.09-0.11 MPa for 72-168 hours to obtain a self-healing epoxy thermal conductive structural adhesive.
[0027] The preparation method of component A is as follows: polysulfide rubber modified epoxy resin and flexible modified epoxy resin are mixed evenly, and then thermal conductive filler is added and dispersed at 1000-1200 rpm for 15-30 minutes under the conditions of 20-30°C and 0.09-0.11 MPa to prepare component A.
[0028] A self-healing method for a self-healing epoxy thermally conductive structural adhesive. The cured epoxy thermally conductive structural adhesive is kept at 100-150°C and 0.1-0.5MPa pressure for 10-30min to achieve self-healing. The conditions are preferably kept at 150°C and 0.1MPa pressure for 30min.
[0029] The self-healing mechanism of the epoxy thermal conductive structural adhesive of the present invention is:
[0030] The epoxy resin and amine curing agent in the composition form a three-dimensional network structure through cross-linking reaction, which provides sufficient rigidity and high shear strength for the structural adhesive; at the same time, after cracks or even colloid fracture occurs, under hot pressing conditions, the phosphorus ions in tributylphosphine carry out nucleophilic attack on the disulfide bonds, causing the disulfide bonds to break and reorganize, and the disulfide bonds to undergo dynamic exchange reactions under the action of the self-healing promoter tributylphosphine to reduce the activation energy, so that the network structure can be rearranged, thereby realizing the self-healing repair of the colloidal material on a macro scale; the addition of flexible epoxy resin in the composition, on the one hand, enters the polymer skeleton network through the redox reaction of epoxy group-amine to provide flexible structural support, and on the other hand, utilizes the flexibility of its molecular chain to maximize the contact of the fracture surface, which can minimize the interference of the thermal conductive filler on the healing exchange reaction.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. The present invention provides a self-healing epoxy-type thermally conductive structural adhesive and a preparation method thereof. The thermally conductive structural adhesive can not only maintain good bonding performance, but also can achieve self-healing of cracks under certain conditions, thus expanding the scope of use and application of the thermally conductive structural adhesive and having broad prospects and important significance.
[0033] 2. The self-healing epoxy thermally conductive structural adhesive provided by the present invention not only maintains good shear strength and appropriate thermal conductivity, but also has the function of self-healing after fracture, so that the thermally conductive structural adhesive can still be repaired under certain conditions even after cracks are generated and fractures occur, thereby extending the service life and further ensuring the safety of the power battery. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0035] The following is a detailed explanation of the present invention in conjunction with the examples. The raw materials used in the examples and comparative examples are all commercially available and are not particularly limited in the present invention.
[0036] The following preparation examples 1 to 3 are used to synthesize polysulfide rubber modified epoxy resin, embodiments 1 to 3 are the preparation of self-healing epoxy-type thermal conductive structural adhesives, comparative example 1 does not contain polysulfide rubber modified epoxy resin, comparative example 2 does not add self-healing accelerator, comparative example 3 does not contain flexible epoxy resin, comparative example 4 uses excessive self-healing accelerator, comparative example 5 replaces tributyl phosphine with diethylenetriamine, and comparative example 6 uses polysulfide rubber modified epoxy resin LPE-3.
[0037] Preparation Example 1
[0038] 100 g of epoxy resin E51 and 66 g of polysulfide rubber JLY124 were weighed; under the protection of an inert atmosphere, addition reaction was carried out at 80° C. for 2 h to obtain polysulfide rubber modified epoxy resin LPE-1 with an epoxy equivalent of 350 g / eq and a disulfide bond content of 15%.
[0039] Preparation Example 2
[0040] 100 g of epoxy resin E51 and 104 g of polysulfide rubber JLY124 were weighed; under the protection of an inert atmosphere, addition reaction was carried out at 80° C. for 2 h to obtain polysulfide rubber modified epoxy resin LPE-2 with an epoxy equivalent of 450 g / eq and a disulfide bond content of 19%.
[0041] Preparation Example 3
[0042] 100 g of epoxy resin E51 and 162 g of polysulfide rubber JLY124 were weighed; under the protection of an inert atmosphere, addition reaction was carried out at 80° C. for 2 h to obtain polysulfide rubber modified epoxy resin LPE-3 with an epoxy equivalent of 620 g / eq and a disulfide bond content of 23%.
[0043] Example 1
[0044] Component A: 20g polysulfide rubber modified epoxy resin LPE-1 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g thermal conductive filler BN-SS was added and dispersed at 1200rpm for 15min under the conditions of 25°C and 0.1MPa;
[0045] Component B: 7.2g amine polymer curing agent JH-5140;
[0046] Component C: 0.156 g of self-healing accelerator tributylphosphine.
[0047] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa can obtain a self-healing epoxy thermal conductive structural adhesive.
[0048] Example 2
[0049] Component A: 20g polysulfide rubber modified epoxy resin LPE-1 and 3g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 10g thermal conductive filler BN-SS was added and dispersed at 1200rpm for 15min under the conditions of 25°C and 0.1MPa;
[0050] Component B: 6.6g amine polymer curing agent JH-5140;
[0051] Component C: 0.046 g of self-healing accelerator tributylphosphine.
[0052] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa can obtain a self-healing epoxy thermal conductive structural adhesive.
[0053] Example 3
[0054] Component A: 20g polysulfide rubber modified epoxy resin LPE-2 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 10.5g thermal conductive filler BN-SS was added and dispersed at 1200rpm for 15min at 25°C and 0.1MPa;
[0055] Component B: 5.4g amine polymer curing agent JH-5140;
[0056] Component C: 0.052g of self-healing accelerator tributylphosphine.
[0057] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa can obtain a self-healing epoxy thermal conductive structural adhesive.
[0058] Comparative Example 1
[0059] The difference from Example 1 is that the polysulfide rubber modified epoxy resin is not contained, specifically:
[0060] Component A: 20g of epoxy resin E-51 and 6g of flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g of thermal conductive filler BN-SS was added and dispersed at 25°C, 0.1MPa, and 1200rpm for 15min;
[0061] Component B: 7.2g amine curing agent JH-5140;
[0062] Component C: 0.052g of self-healing accelerator tributylphosphine.
[0063] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa to obtain an epoxy thermal conductive structural adhesive.
[0064] Comparative Example 2
[0065] The difference from Example 1 is that the self-healing promoter tributylphosphine is not contained, specifically:
[0066] Component A: 20g polysulfide rubber modified epoxy resin LPE-1 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g thermal conductive filler BN-SS was added and dispersed at 25°C, 0.1MPa, and 1200rpm for 15min;
[0067] Component B: 7.2g amine curing agent JH-5140.
[0068] After component A and component B are evenly mixed, they are cured at 25° C. and 0.1 MPa for 96 hours to obtain an epoxy-type thermally conductive structural adhesive.
[0069] Comparative Example 3
[0070] The difference from Example 1 is that it does not contain flexible epoxy resin, specifically:
[0071] Component A: Weigh 20g polysulfide rubber modified epoxy resin LPE-1, add 8.7g thermal conductive filler BN-SS and disperse at 1200rpm for 15min at 25℃ and 0.1MPa;
[0072] Component B: 6g amine curing agent JH-5140;
[0073] Component C: 0.052g of self-healing accelerator tributylphosphine.
[0074] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa to obtain an epoxy thermal conductive structural adhesive.
[0075] Comparative Example 4
[0076] The difference from Example 1 is that the self-healing accelerator tributylphosphine is used in excess, specifically:
[0077] Component A: 20g polysulfide rubber modified epoxy resin LPE-1 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g thermal conductive filler BN-SS was added and dispersed at 25°C, 0.1MPa, and 1200rpm for 15min;
[0078] Component B: 7.2g amine curing agent JH-5140;
[0079] Component C: 0.78g of self-healing accelerator tributylphosphine.
[0080] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa to obtain an epoxy thermal conductive structural adhesive.
[0081] Comparative Example 5
[0082] The difference from Example 1 is that diethylenetriamine is used to replace the self-healing accelerator tributylphosphine, specifically:
[0083] Component A: 20g polysulfide rubber modified epoxy resin LPE-1 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g thermal conductive filler BN-SS was added and dispersed at 25°C, 0.1MPa, and 1200rpm for 15min;
[0084] Component B: 7.2g amine curing agent JH-5140;
[0085] Component C: 0.156 g diethylenetriamine.
[0086] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa to obtain an epoxy thermal conductive structural adhesive.
[0087] Comparative Example 6
[0088] The difference from Example 1 is that the polysulfide rubber modified epoxy resin LPE-3 replaces the polysulfide rubber modified epoxy resin LPE-1, specifically:
[0089] Component A: 20g polysulfide rubber modified epoxy resin LPE-3 and 6g flexible epoxy resin EPCO-1105 were mixed evenly according to the above amounts, and then 11.2g thermal conductive filler BN-SS was added and dispersed at 25°C, 0.1MPa, and 1200rpm for 15min;
[0090] Component B: 7.2g amine curing agent JH-5140;
[0091] Component C: 0.156 g of self-healing accelerator tributylphosphine.
[0092] After mixing component A and component B evenly, add component C and mix evenly. Curing for 96 hours under the conditions of 25° C. and 0.1 MPa to obtain an epoxy thermal conductive structural adhesive.
[0093] The thermally conductive structural adhesives of the above embodiments and comparative examples were subjected to performance tests, and the test methods are as follows:
[0094] 1.Tensile strength and modulus test
[0095] GB / T 1040-2006 was used for the test. Specimens with length, width and thickness of 150mm, 10mm and 2mm were prepared. After 7 days of room temperature curing, three specimens were tested at a test speed of 5mm / min as required by the standard. The test was stopped when the specimen broke. The tensile force was recorded, the tensile strength was calculated, and the average of the test results of the three specimens was taken.
[0096] Table 1 Tensile strength test results
[0097]
[0098] 2. Shear strength test
[0099] The heat-conductive structural adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were coated on the ends of the corona-treated aluminum plates, and the coated surfaces were overlapped. The overlap area was about 25 mm*13 mm. The aluminum plates were cured at 25°C and 0.1 MPa for 96 hours to obtain the aluminum plates with the ends bonded.
[0100] In order to effectively test and calculate the self-healing ability, the bonded 2The aluminum plate was subjected to shear strength test according to the standard GB / T 7124-2008 method, and its shear strength Ks 1 was recorded. The aluminum plate with residual adhesive after the first test was overlapped and self-healed at 150°C and 0.1MPa for 30 minutes. After that, it was taken out and cooled to room temperature for shear strength test, and its shear strength Ks 2 was recorded. The healing efficiency was calculated by the ratio of Ks 2 to Ks 1, and the results are shown in Table 1.
[0101] After the hot pressing treatment of Comparative Example 1, there was no residual adhesive between the two aluminum plates, and a bonding assembly could not be formed, and the self-healing test could not be continued. Therefore, the Ks 2 of Comparative Example 1 was 0.
[0102] Table 2 Shear strength test results before and after healing
[0103]
[0104] 3. Thermal conductivity test
[0105] Use hotdisk to test in accordance with international standard ISO 22007-2. The length and width of the sample is greater than 20*20mm and the thickness is greater than 3mm. Three samples are tested each time for thermal conductivity test. After the test, the sample is cut into two pieces from the side and the cross sections are overlapped together. Self-healing is achieved at 70℃ and 0.1MPa for 30 minutes. Then the thermal conductivity test is performed after the sample is taken out and cooled to room temperature.
[0106] Table 3 Thermal conductivity test results before and after self-healing
[0107]
[0108] As can be seen from the data in Table 2 and Table 3, in Examples 1 to 3, polysulfide rubber modified epoxy resin is used in combination with flexible epoxy resin and self-healing promoter tributyl phosphine. The cured thermal conductive structural adhesive exhibits good shear strength and thermal conductivity, and the colloid is self-healed under the provided conditions after fracture. The healed bonding assembly can still provide high shear strength and good thermal conductivity, showing a high degree of healing. In Comparative Example 1, polysulfide rubber modified epoxy resin is not used. Although the shear strength and thermal conductivity are high, there is no self-healing ability after fracture. In Comparative Example 2, the self-healing promoter tributyl phosphine is not used. Although its colloid material can self-heal after fracture, the healing efficiency is low. In Comparative Example 3, flexible epoxy resin is not used. Although it can self-heal after fracture, the healing efficiency is low due to the hardening of the contact surface. In Comparative Example 4, the self-healing promoter is excessive, and its self-healing efficiency is high, but the shear strength is greatly reduced. Comparative Example 5 uses diethylenetriamine to replace tributylphosphine, and there is no phosphorus ion in the system, thereby reducing the activation energy of the disulfide bond exchange reaction, so the healing efficiency is low. Comparative Example 6 uses polysulfide rubber to modify epoxy resin LPE-3. Since the content of epoxy resin is reduced and the content of disulfide bonds is increased, although the healing rate is high, the shear strength is greatly reduced.
[0109] It can be seen from Table 1 that the self-healing epoxy-type thermally conductive structural adhesive of the embodiment of the present invention has high tensile strength and modulus, and can therefore provide sufficient structural strength. Its high modulus also avoids significant deformation under the action of external forces.
[0110] It can be seen that the self-healing epoxy-type thermally conductive structural adhesive of the present invention, due to the presence of the polysulfide rubber modified epoxy resin component therein, not only ensures the high bonding ability of the structural adhesive through the cross-linking reaction, but also can give the thermally conductive structural adhesive the ability to self-heal through the dynamic exchange reaction of the disulfide bond under the auxiliary action of the self-healing promoter tributylphosphine, thereby extending its service life.
[0111] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A self-healing epoxy thermally conductive structural adhesive, characterized in that: Including component A, component B and component C, calculated by mass: Component A: 20-40 parts of polysulfide rubber modified epoxy resin; 3-15 parts of flexible epoxy resin; 10-25 parts of thermal conductive filler; Component B: 5-15 parts of amine polymer curing agent; Component C: 0.02-0.2 parts of tributylphosphine.
2. The self-healing epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The epoxy equivalent of the polysulfide rubber modified epoxy resin is 300-550 g / eq, and the disulfide bond content is 8-25%.
3. The self-healing epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The disulfide bonds in the polysulfide rubber modified epoxy resin undergo a dynamic exchange reaction under the action of tributylphosphine, causing the network structure to rearrange and realize the self-healing of the epoxy-type thermal conductive structural adhesive.
4. A method for preparing the self-healing epoxy thermally conductive structural adhesive according to claim 1, characterized in that: Mix component A and component B, then add component C and mix evenly, and cure at 20-30° C. and 0.09-0.11 MPa for 72-168 hours to obtain a self-healing epoxy thermal conductive structural adhesive.
5. The preparation method according to claim 4, characterized in that: Component A is prepared by mixing polysulfide rubber modified epoxy resin and flexible modified epoxy resin, adding thermal conductive filler, and dispersing at 1000-1200 rpm for 15-30 minutes at 20-30° C. and 0.09-0.11 MPa.
6. A self-healing method for the self-healing epoxy thermally conductive structural adhesive according to claim 1, characterized in that: The cured epoxy thermal conductive structural adhesive is kept at 100-150° C. and 0.1-0.5 MPa for 10-30 minutes to achieve self-healing.
Citation Information
Cited By
A tail-aware gated dual-view sequential recommendation method for long-tail data distribution
CN122796297A
